Advances in culture and psychology - Chiu, Chi-yue , 1963-; Gelfand, Michele J.; Hong, Ying-yi , 1964- (Oxford University Press, 2011)
The field of culture and psychology is one of the fastest growing areas in the social sciences. As a repeating annual series, Advances in Culture and Psychology will be the first to offer state-of-the-art reviews of scholarly research programs in the growing field of culture and psychology